Does Gamifying in the Marketplace Help in Building Consumer Engagement and Intention to Buy Online? - Rizano, Shantira Ayusha; Salehudin, Imam (Politeknik Negeri Bandung, 2023)
E-commerce is gaining consumer acceptance due to increased internet penetration and advancements in Indonesia. To engage tech-savvy consumers and meet their evolving needs, e-commerce players use gamification by offering personalized shopping experiences, social functionalities, and easy product access. This study examines how Shopee, an e-commerce retailer, can optimize its gamification strategies and intrinsic motivations to encourage customer engagement and impulsive buying behaviour. The study employs purposive sampling to survey 204 respondents and found that gamification and intrinsic motivations positively influence customer shopping engagement. The data was analyzed using Partial Least Squares (PLS) with the SmartPLS software. The findings show that gamification and intrinsic motivations hold a positive influence on shopping engagement. Furthermore, socialness and shopping enjoyment lead to increased impulsive buying behavior. Notably, shopping engagement emerges as a critical factor positively shaping users' intention to continue using online shopping applications.